Penentuan Zona Dan Karakteristik Daerah Aliran Sungai Dengan Analisa Spasial Sistem Informasi Geografis - Era Alfansyuri -; Indra Farni - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
Watershed Management comprehensively considers the boundaries and characteristics of physical watersheds that have precision and detail of data sources. Determination of the Watershed zone in a digital process is supported by the development of satellite-based remote sensing surface data and supported by spatial data analysis management technology with Geographic Information System. Provincial spatial boundaries and watershed characteristics include the area, slope and land use in the area so as to support the watershed management.